Identification of plasma exosomes long non-coding RNA HAGLR and circulating tumor cells as potential prognosis biomarkers in non-small cell lung cancer - Rao, Le; Luo, Lihua; Luo, Liufang; Chen, Shan; Ran, Ruizhi; Liu, Xianling (Translational Cancer Research, 2019)
Background: The main purpose of this study was to identify the correlation between the expression of long non-coding RNA (lncRNA) HAGLR in plasma exosomes and the detection rate of circulating tumor cells (CTCs) in patients with non-small cell lung cancer (NSCLC). Methods: LncRNA HAGLR expression was detected in plasma exosomes of 40 patients with NSCLC and 8 healthy subjects using qRT-PCR. CTCs were enriched and separated using CTC-BIOPSY® abnormal cell separator. The correlations between lncRNA HAGLR expression in plasma exosomes and CTCs of patients with NSCLC and clinical pathological parameters were also analyzed. Bioinformatics analyses indicated HAGLR was evidently down-regulated in NSCLC tissues when compared to normal controls. The relationship between differential expression of HAGLR with different stages of NSCLC and clinical prognosis were elucidated using corresponding statistical methods. Results: HAGLR was significantly decreased in NSCLC, and there was obvious correlation with overall survival (P